The Assessment of Competency in Thoracic Sonography (ACTS) scale: validation of a tool for point-of-care ultrasound - Millington, Scott J.; Arntfield, Robert T.; Guo, Robert Jie; Koenig, Seth; Kory, Pierre; Noble, Vicki; Mallemat, Haney; Schoenherr, Jordan R. (Critical ultrasound journal, 2017)
Background The rapid adoption of point-of-care ultrasound (POCUS) has created a need to develop assessment tools to ensure that learners can competently use these technologies. In this study, the authors developed and tested a rating scale to assess the quality of point-of-care thoracic ultrasound studies performed by novices. In Phase 1, the Assessment of Competency in Thoracic Sonography (ACTS) scale was developed based on structured interviews with subject matter experts. The tool was then piloted on a small series of ultrasound studies in Phase 2. In Phase 3 the tool was applied to a sample of 150 POCUS studies performed by ten learners; performance was then assessed by two independent raters. Results Evidence for the content validity of the ACTS scale was provided by a consensus exercise wherein experts agreed on the general principles and specific items that make up the scale. The tool demonstrated reasonable inter-rater reliability despite minimal requirements for evaluator training and displayed evidence of good internal structure, with related scale items correlating well with each other. Analysis of the aggregate learning curves suggested a rapid early improvement in learner performance with slower improvement after approximately 25–30 studies. Conclusions The ACTS scale provides a straightforward means to assess learner performance. Our results support the conclusion that the tool is an effective means of making valid judgments regarding competency in point-of-care thoracic ultrasound, and that the majority of learner improvement occurs during their first 25–30 practice studies.